Beyond Matriculation: Examining Factors That Contribute to African American Male Persistence at a Predominantly White Institution. (November 2019) - Simmons, Lamont D.
In higher education, academic disparities exist between African American males and their gender and ethnic counterparts. Furthermore, many institutions struggle to promote African American male persistence beyond matriculation. This study provides insight into how a sample of undergraduate African American males was persisting at a predominantly White institution. Six themes emerged, including (a) exposure to rigorous high school curriculum, (b) feeling encouraged and supported, (c) having a sense of motivation, (d) educational aspirations beyond a bachelor's degree, (e) involvement in ethnic-based campus organizations, and (f) connecting with minority faculty. The preponderance of findings demonstrates that noncognitive factors are essential to how African American males persist.